2015
DOI: 10.4081/monaldi.2013.104
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarette: a possible substitute for cigarette dependence

Abstract: Cigarette smoking is the leading cause of premature mortality in western countries and it is important for smokers to stop as early as possible. Electronic cigarettes are a popular phenomenon of global proportion. Recent uncontrolled studies, reported that a certain number of smokers have quit using electronic cigarettes. This could hint a role for electronic cigarettes to be used for smoking cessation, and therefore merits further evaluation for this purpose. Besides vaporising nicotine to be inhaled, electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 41 publications
1
63
0
3
Order By: Relevance
“…Though final consensus has not been reached (Caponetto et al, 2013;Geiss et al, 2015;Wagener et al, 2012), some studies suggest that e-cigarette products may reduce risk and offer a safer alternative (Farsalinos et al, 2014) to combustible cigarettes for consumers and people exposed to second-hand smoke (Colard et al, 2015;Czogala et al, 2013;Mcauley et al, 2012;Schripp et al, 2013) when liquid formulation and devices are adequately controlled and regulated (American Industrial Hygiene Association, 2014;Cahn & Siegel, 2011;Trehy et al, 2011). Consequently, the need to apply strict and accurate methodologies to assess e-cigarette products is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Though final consensus has not been reached (Caponetto et al, 2013;Geiss et al, 2015;Wagener et al, 2012), some studies suggest that e-cigarette products may reduce risk and offer a safer alternative (Farsalinos et al, 2014) to combustible cigarettes for consumers and people exposed to second-hand smoke (Colard et al, 2015;Czogala et al, 2013;Mcauley et al, 2012;Schripp et al, 2013) when liquid formulation and devices are adequately controlled and regulated (American Industrial Hygiene Association, 2014;Cahn & Siegel, 2011;Trehy et al, 2011). Consequently, the need to apply strict and accurate methodologies to assess e-cigarette products is essential.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Proponents of e-cigarettes maintain that these products emulate smoking behavior without exposing the user to the toxic smoke constituents of conventional cigarettes that are deleterious to health, so there would be a public health benefit if individual smokers completely switched or substantially reduced their cigarette smoking habit. [18][19][20] However, the use of e-cigarettes could be a problem at the population level. For instance, e-cigarettes could fuel and promote nicotine addiction, especially in children, and their acceptance has the potential to renormalize smoking behavior.…”
mentioning
confidence: 99%
“…23,24 However, many youths use e-cigarettes for novelty and flavors rather than to quit smoking. 25 Our study confirmed that current youth smokers who reported use of flavored e-cigarettes had a significantly lower intention to quit tobacco use in the next 12 months (aOR = 0.6; P = .006) compared with those who reported not using e-cigarettes.…”
mentioning
confidence: 99%